Emotional Regulation Among Athletes with Disabilities - Rafinaxa Fathir Arisislam; Eva Nandha Jalma Yael; Endang Lestari; Maya Nisaul Magfiroh; Miftakhul Jannah (International Conference on Psychology and Education (ICPE), 2023)
People with disabilities often find it difficult to achieve emotional balance, especially those who become professional athletes. This study aims to discuss the regulation of emotions in athletes with disabilities in East Java. This research approach uses a quantitative descriptive method. The population in this study were athletes with disabilities NPCI East Java with a total of 69 people with an age range of 14-57 years and gender as many as 56 men and 13 women. To obtain data, this study used Gross and Thompson's (2007) emotional regulation scale. The data analysis technique used descriptive statistics presented in tabular form. Based on the results of data analysis, it was found that out of 69 athletes with disabilities, there were 19 people with a low level of emotional regulation, 49 people with a moderate level of emotional regulation, and 1 person with a high level of regulation.